Preparação e caracterização de complexos multicomponentes contendo ciclodextrinas e benznidazol - Melo, Polyanne Nunes de (2013)
The benznidazole (BNZ) is the only alternative for Chagas disease treatment in Brazil. This drug has low solubility, which restricts its dissolution rate. Thus, the present work aimed to study the BNZ interactions in binary systems with beta cyclodextrin (β-CD) and hydroxypropyl-beta cyclodextrin (HP-β-CD), in order to increase the apparent aqueous solubility of drug. The influence of seven hydrophilic polymers, triethanolamine (TEA) and 1-methyl-2- pyrrolidone (NMP) in benznidazole apparent aqueous solubility, as well as the formation of inclusion complexes was also investigated. The interactions in solution were predicted and investigated using phase solubility diagram methodology, nuclear magnetic resonance of protons (RMN) and molecular modeling. Complexes were obtained in solid phase by spray drying and physicochemical characterization included the UV-Vis spectrophotometric spectroscopy in the infrared region, scanning electron microscopy, X-ray diffraction and dissolution drug test from the different systems. The increment on apparent aqueous solubility of drug was achieved with a linear type (AL) in presence of both cyclodextrins at different pH values. The hydrophilic polymers and 1-methyl-2-pyrrolidone contributes to the formation of inclusion complexes, while the triethanolamine decreased the complex stability constant (Kc). The log-linear model applied for solubility diagrams revealed that both triethanolamine and 1-methyl-2-pyrrolidone showed an action cosolvent (both solvents) and complexing (1-methyl-2-pyrrolidone). The best results were obtained with complexes involving 1-methyl-2-pyrrolidone and hydroxypropylbeta- cyclodextrin, with an increased of benznidazole solubility in 27.9 and 9.4 times, respectively. The complexes effectiveness was proven by dissolution tests, in which the ternary complexes and physical mixtures involving 1-methyl- 2-pyrrolidone and both cyclodextrins investigated showed better results, showing the potential use as novel pharmaceutical ingredient, that leads to increased benznidazole bioavailability